The analysis of alpha‐1‐antitrypsin glycosylation with direct LC‐MS/MS. Issue 18 (26th February 2018) - Yin, Haidi; An, Mingrui; So, Pui‐kin; Wong, Melody Yee‐Man; Lubman, David M.; Yao, Zhongping
Abstract: A liquid chromatography‐tandem mass spectrometry (LC‐MS/MS)‐based methodology has been developed to differentiate core‐ and antennary‐fucosylated glycosylation of glycopeptides. Both the glycosylation sites (heterogeneity) and multiple possible glycan occupancy at each site (microheterogeneity) can be resolved via intact glycopeptide analysis. The serum glycoprotein alpha‐1‐antitrypsin (A1AT) which contains both core‐ and antennary‐fucosylated glycosites was used in this study. Sialidase was used to remove the sialic acids in order to simplify the glycosylation microheterogeneity and to enhance the MS signal of glycopeptides with similar glycan structures. β1‐3, 4 galactosidase was used to differentiate core‐ and antennary‐fucosylation. In‐source dissociation was found to severely affect the identification and quantification of glycopeptides with low abundance glycan modification. The settings of the mass spectrometer were therefore optimized to minimize the in‐source dissociation. A three‐step mass spectrometry fragmentation strategy was used for glycopeptide identification, facilitated by pGlyco software annotation and manual checking. The collision energy used for initial glycopeptide fragmentation was found to be crucial for improved detection of oxonium ions and better selection of Y1 ion (peptide+GlcNAc). Structural assignments revealed that all three glycosylation sites of A1AT glycopeptides contain complex N‐glycan structures: site Asn70 contains biantennary glycans without fucosylation; site Asn107 contains bi‐, tri‐ and tetra‐antennary glycans with both core‐ and antennary‐fucosylation; site Asn271 contains bi‐ and tri‐antennary glycans with both core‐ and antennary‐fucosylation. The relative intensity of core‐ and antennary‐fucosylation on Asn107 was similar to that of the A1AT protein indicating that the glycosylation level of Asn107 is much larger than the other two sites.